Transpiration and whole-tree conductance in ponderosa pine trees of different heights - Ryan, M G; Bond, B J; Law, B E; Hubbard, R M; Woodruff, D; Cienciala, E; Kucera, J (Oecologia, 2000)
Changes in leaf physiology with tree age and size could alter forest growth, water yield, and carbon fluxes. We measured tree water flux (Q) for 14 ponderosa pine trees in two size classes (12 m tall and ∼40 years old, and 36 m tall and ∼ 290 years old) to determine if transpiration (E) and whole-tree conductance (g t) differed between the two sizes of trees. For both size classes, E was approximately equal to Q measured 2 m above the ground: Q was most highly correlated with current, not lagged, water vapor pressure deficit, and night Q was <12% of total daily flux. E for days 165-195 and 240-260 averaged 0.97 mmol m-2 (leaf area, projected) s-1 for the 12-m trees and 0.57 mmol m-2 (leaf area) s-1 for the 36-m trees. When photosynthetically active radiation (I P) exceeded the light saturation for photosynthesis in ponderosa pine (900 µmol m-2 (ground) s-1), differences in E were more pronounced: 2.4 mmol m-2 (leaf area) s-1 for the 12-m trees and 1.2 mmol m-2 s-1 for the 36-m trees, yielding g t of 140 mmol m-2 (leaf area) s-1 for the 12-m trees and 72 mmol m-2 s-1 for the 36-m trees. Extrapolated to forests with leaf area index =1, the 36-m trees would transpire 117 mm between 1 June and 31 August compared to 170 mm for the 12-m trees, a difference of 15% of average annual precipitation. Lower g t in the taller trees also likely lowers photosynthesis during the growing season.
Keywords: Hydraulic conductance; Whole-tree conductance; Humidity response of stomatal conductance; Key words Transpiration